Experiences of employees in a public sector organisation during periods of uncertainty and instability : exploring the nexus between employee empowerment and organisational agility - Olivier, Johan (University of Pretoria, 2025)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2024.